Related-key impossible boomerang cryptanalysis on TWINE - Min XIE; Feng TIAN; Jiaqi LI (Tongxin xuebao)
In order to evaluate the security of the lightweight block cipher TWINE,the method of related-key impossible boomerang cryptanalysis was applied and a related-key impossible boomerang distinguisher consisting of 16-round and 17-round paths was constructed.Based on this new distinguisher,an attack on 23-round TWINE was mounted successfully by concatenating 4-round to the beginning and 2-round for the 17-round path and 3-round for the 16-round path to the end respectively.The attack on 23-round TWINE required data complexity of only 2 62.05plaintexts and computational complexity of about 2 70.4923-round encryptions.Compared with published cryptanalysis results,the proposed attack has obvious advantages.